The Utilizing Of Video Maker As A Media In Writing Greeting Card At Junior High School 1 Mantiat Pari : Pemanfaatan Video Maker Sebagai Media Dalam Menulis Kartu Ucapan di SMP Negeri 1 Mantiat Pari - Dina Novita Sari; Indra Perdana; Ristati Ristati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Media is one of the essential things in the teaching-learning process. One of them is video maker. Video maker is one of the applications that can be used as a media in teaching writing. The research aim is to see the utilizing of video maker as a media in writing greeting cards. There were sixteen students as a sample, especially eighth grades students. The researcher gave them ten items’ of questionnaires. The findings of this research can be divided into two categories. The first was video maker gave the students motivation in learning English. They were in statement one (84,44%) statement two (94,44%), statement four (88,89%), and statement six (93,33%). All of the statements have category very high. It meant video maker gives the students motivation to learn writing. The second was the students interested in using video maker as a media in writing. They were in the third statement (81,11%) and the category was very high, the fifth statement (83,33%) and the sort was very high, the eighth statement (76,67%) and the sort was high, the ninth statement (68,89%) and the sort was high, the tenth statement (86,67%) and the sort was very high. There was no questionnaire in medium, low or very low levels. Based on the result, it can be concluded that the utilization of video maker as a media in writing at SMPN-1 Mantiat Pari was positive. The students gave a positive response to it.